Unbiased analysis of the impact of micropatterned biomaterials on macrophage behaviour provides insights beyond pre-defined polarisation states - Singh, Sonali; Awuah, Dennis; Rostam, Hassan; Emes, Richard; Kandola, Navrohit K.; Onion, David; Htwe, Su Su; Rajchagool, Buddharaksa; Cha, Byung-Hyun; Kim, Duckjin; Tighe, Patrick; Vrana, Nihal Engin; et al. (American Chemical Society, 2017)
Macrophages are master regulators of immune responses towards implanted biomaterials. The activation state adopted by macrophages in response to biomaterials determines their own phenotype and function as well as those of other resident and infiltrating immune and non-immune cells in the area. A wide spectrum of macrophage activation states exists, with M1 (pro-inflammatory) and M2 (anti-inflammatory) representing either ends of the spectrum. In biomaterials research, cellinstructive surfaces that favour or induce M2 macrophages have been considered as beneficial due to the anti-inflammatory and pro-regenerative properties of these cells. In this study, we used a gelatin methacryloyl (GelMA) hydrogel platform to determine whether micropatterned surfaces can modulate the phenotype and function of human macrophages. The effect of microgrooves/ridges and micropillars on macrophage phenotype, function, and gene expression profile were assessed using conventional methods (morphology, cytokine profile, surface marker expression, phagocytosis) and gene microarrays. Our results demonstrated that micropatterns did induce distinct gene expression profiles in human macrophages cultured on microgrooves/ridges and micropillars. Significant changes were observed in genes related to primary metabolic processes such as transcription, translation, protein trafficking, DNA repair and cell survival. However, interestingly conventional phenotyping methods, relying on surface marker expression and cytokine profile, were not able to distinguish between the different conditions, and indicated no clear shift in cell activation towards an M1 or M2 phenotypes. This highlights the limitations of studying the effect of different physicochemical conditions on macrophages by solely relying on conventional markers that are primarily developed to differentiate between cytokine polarised M1 and M2 macrophages. We therefore, propose the adoption of unbiased screening methods in determining macrophage responses to biomaterials. Our data clearly shows that the exclusive use of conventional markers and methods for determining macrophage activation status could lead to missed opportunities for understanding and exploiting macrophage responses to biomaterials.